Everybody writes : your new and improved go-to guide to creating ridiculously good content - Handley, Ann, 1963- (Ascent Audio, 2023)
In the newly revised and updated edition of Everybody Writes, marketer and author Ann Handley improves on her Wall Street Journal bestselling book that's helped hundreds of thousands become better, more confident writers. In this brand-new edition, she delivers all the practical, how-to advice and insight you need for the process and strategy of content creation, production, and publishing. This new edition also includes: all-new examples, tools, resources; an updated step-by-step writing framework; added and expanded chapters that reflect the evolution of content marketing (and evolution of Ann's thinking about what works today); the same witty and practical how-to approach; how to attract and retain customers with stellar online communication; how to choose your words well, sparingly, and with honest empathy for your customers; best practices and ideas for crafting credible, trustworthy content; and more. Content marketing has evolved. Yet writing matters more than ever. In this new edition of Everybody Writes, you'll find the strategies, techniques, tips, and tools you'll need to refine, upgrade, and (most of all) inspire your own best content marketing.